Tinjauan Ketidakpuasan Pasien Lama Terhadap Pelayanan Pendaftaran Rawat Jalan Di Rumah Sakit Menteng Mitra Afia - Nur Endah Sari; Gama Bagus Kuntoadi (APIKES Bhumi Husada Jakarta, 2018)
ABSTRACT The hospital is one of the health service facilities chosen by the community in obtaining health services. Registration is the initial gate of a hospital service, this is where the important role of the registration officer, must be able to give a comfortable impression so that patients can feel the satisfaction of hospital services. Patient satisfaction consists of 5 dimensions namely tangible, responsiveness, reliability, assurance, and empathy. This research was conducted based on 5 dimensions of service quality, which was felt by old patients towards outpatient registration officers, namely the statement